Octreotide infusion as a treatment for hepatic hydrothorax in a hospital-at-home program: case report from Mayo Clinic - Igor Dumic; Margaret R. Paulson; Michael J. Maniaci; Leah W. Webster; Corey Wachter; Andrew Turunen; Charles W. Nordstrom (Therapeutic Advances in Gastroenterology)
Hepatic hydrothorax (HH) is a rare but serious complication of end-stage liver disease that is often refractory to conventional medical and procedural management. This case report describes a 75-year-old woman with HH secondary to cirrhosis from metabolic-associated steatotic liver disease. Her clinical course was marked by recurrent hospitalizations, refractory right-sided pleural effusion, and multiple unsuccessful interventions including diuretics, serial thoracenteses, an indwelling pleural catheter, and chemical pleurodesis. Notably, the persistence of pleural fluid despite resolution of ascites ultimately led to the formation of a thoracic fistula, with pleural drainage volumes exceeding 4 L/day. Further invasive procedures, such as transjugular intrahepatic portosystemic shunt or liver transplantation, were declined by the patient. She was enrolled in Mayo Clinic’s hospital-at-home (HaH) program, where continuous intravenous octreotide was initiated at a dose of 25 mcg/h. This resulted in a significant reduction in pleural output—from over 4000 mL to less than 100 mL daily. After clinical stabilization, the patient transitioned to subcutaneous octreotide and remained clinically stable for over 6 months, with improved quality of life and no significant adverse effects. To our knowledge, this is the first reported case of continuous intravenous octreotide infusion for HH administered safely in a home-based acute care setting. This case underscores the potential therapeutic role of octreotide in managing refractory HH and highlights the feasibility of delivering complex cirrhosis-related care through a HaH model with multidisciplinary collaboration. Further research is warranted to assess the long-term efficacy, safety, and cost-effectiveness of octreotide in this context and to explore broader application in home hospital environments.